Analysis of Global Challenges in Contemporary Islamic Education on the Implementation of a Love Based Curriculum in Madrasahs - Marlina Marlina; Selvi Ratna Sari; Zuhdiyah Zuhdiyah; Maryamah Maryamah; Nyayu Soraya (CV. Bimbingan Belajar Assyfa, 2026)
Contemporary Islamic education in madrasahs faces increasingly complex global challenges, such as cultural globalization, the rapid development of digital technology, a crisis of humanitarian values, and shifts in students’ characteristics. These challenges demand a curricular approach that goes beyond a sole focus on the cognitive and normative aspects of Islamic teachings, placing greater emphasis on character development and the reinforcement of humanitarian values. This article aims to analyze the global challenges faced by contemporary Islamic education and to examine the implementation of a love-based curriculum in madrasahs as an alternative, humanistic, and transformative educational approach. The study employs a qualitative method through library research by analyzing various scholarly literature, Islamic educational concepts, and curriculum policy documents. The findings indicate that a love-based curriculum is relevant in addressing the global challenges of Islamic education by instilling values of compassion, empathy, tolerance, religious moderation, and social concern within the learning process. The implementation of a love-based curriculum in madrasahs is expected to shape learners who possess strong faith, noble character, and a balanced sense of social and spiritual awareness. Thus, a love-based curriculum becomes a vital strategy in strengthening the role of madrasahs as Islamic educational institutions that are adaptive to global developments without losing their Islamic identity.